Impact of Embedment Depth and Thickness on Behavior of Diaphragm Wall - Aakash Rajeshkumar Suthar, Yogeshkumar S Patel (Mathematical Statistician and Engineering Applications, 2022)
In current scenario due to rapid urbanization and due to increase in population there is a demand in development of infrastructure. Horizontal development is not the solution to this problem due to scarcity of land. The only solution is the vertical development and to accommodate the vertical development larger size basement will be required for parking and for many other purposes. Diaphragm wall is a reinforced concrete structure that will support the adjacent soil. In the present research, behavior of diaphragm wall was analyzed for one and two basements. For one basement thickness of diaphragm wall is varied from 0.5 meter to 0.7 meter. For two basement diaphragm walls, the depth of embedment was varied for 4 meters to 8 meter in the ground. The analytical analysis as well as software base analysis was performed in the research. It has been concluded that with the increase in thickness and embedment depth, the stability of diaphragm wall also increases.